Gene flow between cultivated and wild sunflower Helianthus annuus in Argentina - Ureta, Maria Soledad (2008)
Naturalized populations of wild sunflower, Helianthus annnus, occur in six provinces of central Argentina, usually near sunflower crops. Plants of intermediate morphology indicate that gene flow might take place in both senses. In order to quantify gene flow between cultivated and wild sunflower, an experimental stand of sunflower was sown surrounded by plots of wild plants at increasing distances. Hybridization rate was estimated using a crop specific isozyme marker, and a mean of 7% progenies were crop-wild hybrids. The nearest wild plants (3 m from the cultivar) showed the highest percentage (18%) of gene flow, which was found to decrease with distance, up to 500 m. Pollen flow from wild plants to crop, evaluated through morphological characters in the progenies of cultivated plants from a stand invaded by wild sunflowers, produced 3.75% intermediate plants.